1994
DOI: 10.1002/cm.970280203
|View full text |Cite
|
Sign up to set email alerts
|

Purification of microtubule proteins from Xenopus egg extracts: Identification of a 230K MAP4‐like protein

Abstract: We describe the purification of microtubule proteins from Xenopus egg extracts by temperature-dependent assembly and disassembly in the presence of dimethyl sulfoxide and identify a number of presumptive microtubule-associated proteins (MAPs). One of these proteins has a molecular weight of 230 kDa and is immunologically related to HeLa MAP4. We show that this MAP is heat stable and phosphorylated, and that it promotes elongation of microtubules from axonemes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…MAP4 was considered a likely candidate, as well as other related ones (e.g. XMAP from Xenopus eggs, Faruki and Karsenti (1994)). Regarding kinases, cdc2 and MAP kinases were suggested as potential triggers of microtubule reorganization (Gotoh et al, 1991;Verde et al, 1992;Lieuvin et al, 1994;Ookata et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…MAP4 was considered a likely candidate, as well as other related ones (e.g. XMAP from Xenopus eggs, Faruki and Karsenti (1994)). Regarding kinases, cdc2 and MAP kinases were suggested as potential triggers of microtubule reorganization (Gotoh et al, 1991;Verde et al, 1992;Lieuvin et al, 1994;Ookata et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Scale bars are 25 µm in A and 10 µm in B. 1994; Faruki and Karsenti, 1994;Gard and Kirschner,1987b;Jessus et al, 1985;Shiina et al, 1992). Results from in vitro studies have shown that XMAP230 (Anderson et al, 1994) and XMAP310 Anderson and Karsenti, 1997) stabilize MTs and suppress dynamic instability in vitro, similar to the effects of MAPs isolated from vertebrate brain (Drechsel et al, 1992;Pryer et al, 1992).…”
Section: Regulation Of Mt Assembly and Organizationmentioning
confidence: 90%
“…MAPs are good substrates for many protein kinases in vitro [21], and their phosphorylation was shown to reduce the ability of MTs to polymerize in vitro [22]. MAPs include tau and MAP2, which are expressed abundantly only in nervous tissue, and MAP4, expressed ubiquitously in non-neuronal cells [23]. The phosphorylation state of MAP4 is thought to be a key factor in the regulation of MT stability.…”
Section: Introductionmentioning
confidence: 99%